ANTIGENOTOXIC EFFECTS OF MELATONIN AGAINST CHROMOSOME DAMAGE INDUCED BY 7,12- DYMETHYLBENZ(a)ANTHRACENE - & Mohammed, Omar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The carcinogen 7,12-dimethylbenz(a)anthracene (DMBA) is a model of Polyaromatic hydrocarbons (PAHs) which is metabolized to DMBA-trans-3,4-diol, an intermediate inductive of DNA mutations through alteration of DNA base pairs, initiation of chronic inflammation and excessive production of Reactive Oxygen Species which is very toxic substances in tissue. This study was aimed to investigate the preventive effects of Melatonin. DNA damage was induced by topical treatment of DMBA to the shaven part of mice skin. Animals injected with melatonin (10 mg/kg ) intraperitoneally. mice bone marrow cells were used for the determination of chromosomal aberrations, micronuclei and the percentage of mitotic index. DMBA induced significant elevations in structural chromosome abnormalities, micronuclei, and caused a significant decreases in the mitotic index. The pre-treatment group (Me + DMBA) greatly reduced the number of CA and enhanced MI frequency compared to DMBA treated animals. statistical analysis showed that the number of induced Di-MN and Tri –MN in pre and post treatment groups were decreased significantly compared with the positive control.